A escrita colaborativa em ambientes digitais: o uso da ferramenta wiki como prática de letramento digital com alunos do nono ano do Ensino Fundamental II - Allyson Mendes Rosa (2021)
The school setting has always prioritized individualized writing, pencil and paper being its main technologies. However, as a result of my own professional experience in a public school within a socially vulnerable context I have observed that writing in digital environments impacts the lives of students more effectively than the once prominent writing models of the past. WhatsApp, Facebook and Instagram, environments which make use of writing as the foremost tool for sharing ideas and social customs, are significantly more inviting to the current generation of students. Nevertheless, being in those digital environments does not necessarily mean that students know how to use linguistic, graphical, or interface resources in an independent manner. In this work I lay out a Collaborative Writing teaching project designed for students in the 9th year of Ensino Fundamental II (elementary school) of Escola Estadual Silviano Brandão, in Belo Horizonte, state of Minas Gerais, by means of collaborative Wiki writing. This writing practice’s main strategy is the development of reading and writing proficiency, as well as improvements in digital literacy and Multiliteracies of students. This teaching project has as a methodological focus a proposal of intervention research dealing in a qualitative manner as well as in multiliteracy from Rojo (2008); Novais, Ribeiro, and D’Andréa (2011); Dell’Isola (2012); and Paiva (2012, 2013, 2020). The premises in Pinheiro (2011) and Felipeto (2019) have also been followed. The systematic teaching project built around organized activities of collaborative text writing meant for the evaluation of reading and writing performance of my students unfortunately could not take place due to the coronavirus pandemic, serving only as optional suggested activities.